Realization of an optimum mode of formation of a dose of liquid production by weight metod - Mykhailyk, Borys; Gavva, Oleksandr M. (My University, 2018)
In this work was deduced rational function of the dosing for the mechatronic module of weight dosing for liquid products. To provide correct the application of mathematically derived functions, the synthesis of the pneumo drive was performed, for the pre-calculated common types of shut-off valves of various forms of valves (tapered, spherical with a nozzle that does not repeat the shape of the valve, spherical with a nozzle that repeats the form of the valve, cylindrical). Implementation, performed taking into account the accepted parameters of production, packaging, method of execution. The mathematical connection between the coordinate of the valve position and the function of the receipt of products in the container was established, which in turn gave the opportunity to derive the optimal function of movement of the valve of the shut-off valve.
Keywords: мехатронній модуль вагового дозування; запірна арматура; клапан; раціональне дозування; закон руху; пневматичний привід; mechatronic module of weight dosing; shut-off valves; valve; rational dosing; movement function; pneumatic drive; мехатронный модуль весового дозирования; запорная арматура; рациональное дозироване; закон движения; пневматический привод; кафедра машин і апаратів харчових та фармацевтичних виробництв